Hubungan Pesantren dengan Madrasah di Indonesia - Santoso, Baron; Anshory, Muhammad Isa (TSAQOFAH, 2024)
Islamic boarding schools and Madrasas are Islamic educational institutions spread across Indonesia. This research aims to review the history of Islamic boarding schools and madrasas in Indonesia, as well as the relationship between Islamic boarding schools and Madrasas. In this research, library research or library research methods are used. The emergence of madrasas is an effort to renew and bridge the relationship between the traditional system (Islamic boarding school) and the modern education system. And this is also an effort to improve the education system in Islamic boarding schools towards an education system that is more likely to enable graduates to get the same opportunities as those in public schools. In the madrasa system, there does not have to be a boarding house, mosque and recitation of classical books. The elements that are prioritized in madrasas are leaders, teachers, students, hardware, software and teaching of Islamic religious subjects.